1995
DOI: 10.1073/pnas.92.3.664
|View full text |Cite
|
Sign up to set email alerts
|

Protein-tyrosine-phosphatase SHPTP2 is a required positive effector for insulin downstream signaling.

Abstract: SHPTP2 is a ubiquitously expressed tyrosine-specific protein phosphatase that contains two aminoterminal Src homology 2 (SH2) domains responsible for its association with tyrosine-phosphorylated proteins. In this study, expression ofdominant interfering mutants of SHPTP2 was found to inhibit insulin stimulation of c-fos reporter gene expression and activation of the 42-kDa (Erk2) and 44-kDa (Erkl) mitogen-activated protein kinases. Cotransfection of dominant interfering SHPTP2 mutants with v-Ras or Grb2 indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
191
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(213 citation statements)
references
References 52 publications
21
191
1
Order By: Relevance
“…Similarly, Yamauchi et al (1995) found that a dominant negative form of SHP-2 blocked insulin stimulation of Erk1 and Erk2 activation, suggesting an involvement of SHP-2 in stimulation of the MAP kinase cascade.…”
Section: Identi®cation Of Tyr763 As An Autophosphorylation Site In Thmentioning
confidence: 78%
“…Similarly, Yamauchi et al (1995) found that a dominant negative form of SHP-2 blocked insulin stimulation of Erk1 and Erk2 activation, suggesting an involvement of SHP-2 in stimulation of the MAP kinase cascade.…”
Section: Identi®cation Of Tyr763 As An Autophosphorylation Site In Thmentioning
confidence: 78%
“…The insulin receptor is a protein tyrosine kinase which, when activated by insulin binding, undergoes rapid autophosphorylation and phosphorylates intracellular protein substrates, including insulin receptor substrates (IRSs-IRS-1 and IRS-2 are the most important) [9,10,11] and Shc [12]. Following tyrosine phosphorylation, the IRSs act as docking proteins for several Src homology 2 domaincontaining proteins, including phosphatidylinositol 3-kinase (PI3-kinase), Grb2, SHP2, Nck and Fyn [13,14,15,16,17]. Downstream to PI 3-kinase there is activation of a serine/threonine kinase, Akt [18].…”
mentioning
confidence: 99%
“…These results suggest that SRC or some other SRC family kinase may contribute to LPA-induced tyrosine phosphorylation of SHPS-1 and its association with SHP-2. Milarski and Saltiel, 1994;Xiao et al, 1994;Yamauchi et al, 1995) or EGF (Bennett et al, 1996), indicating that SHP-2 may mediate this response. To investigate the physiological consequences of SHPS-1-SHP-2 complex formation in response to LPA, we examined the e ects of overexpression of a catalytically inactive SHP-2 or of SHPS-1 on LPA-induced MAP kinase activation in CHO cells.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in response to insulin, SHP-2 binds via its SH2 domains to IRS-1, a major substrate for the insulin receptor tyrosine kinase (Sun et al, 1991) and is thereby activated (Kuhne et al, 1993;Matozaki et al, 1995;Pluskey et al, 1995). The expression of a catalytically inactive SHP-2 inhibits insulin-induced activation of RAS and mitogen-activated protein (MAP) kinase (Noguchi et al, 1994;Milarski and Saltiel, 1994;Xiao et al, 1994;Yamauchi et al, 1995) as well as EGF-induced MAP kinase activation (Bennett et al, 1996) and thereby blocks DNA synthesis and cell proliferation. Moreover, microinjection of RNAs encoding catalytically inactive SHP-2 into Xenopus oocytes induces marked posterior truncation and inhibits ®broblast growth factor-and activin-mediated mesoderm induction (Tang et al, 1995).…”
Section: Introductionmentioning
confidence: 99%